Food Delivery App Usability on Purchase Decision of Young Consumers: Inputs for Enhancement - Aranda, Ariane; Arcipe, Yvonne Marie; Balanquit, Ma. Jonah; Manadong, Eunice; Mayuyo, Princess Diana (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined food delivery app usability and its influence on the purchase decisions of young consumers. Anchored on the Input–Process–Output model, the study focused on usability dimensions such as ease of navigation, user interface and design, speed and performance, personalization features, security and privacy, customer support and assistance, and influence on purchase decision. The study employed a descriptive research design using the survey method. Data were gathered through a validated survey questionnaire administered to 75 Marketing students from the College of Business and Public Administration of Eulogio “Amang” Rodriguez Institute of Science and Technology, selected through purposive sampling. The data were analyzed using percentage, weighted mean, Likert scale interpretation, and Pearson r. Findings showed that young consumers assessed food delivery app usability to an extent, with a grand mean of 4.18. User interface and design, security and privacy, and personalization features were the strongest areas, while speed and performance received the lowest assessment. The influence of food delivery app usability on purchase decision was rated to a high extent, with a grand mean of 4.21, indicating that usability affects ordering behavior and recommendation intention. Significant relationships were also reported involving consumer profile and app usability assessment. The study concluded that improved usability contributes to customer satisfaction and stronger purchasing behavior. The study aligns with SDG 8, SDG 9, and SDG 12 by supporting digital commerce, innovation in service platforms, and informed consumer decision-making. Its sustainability impact lies in promoting user-centered, reliable, and responsive food delivery applications that support technological, socio-economic, business, and institutional sustainability.